A Comprehensive Study of Effects of Renewable Energy Based Electric Vehicles on Environment - Hossain, Md. Taufiq; Khan, Saidul Islam; Dodaev, Zohar Al (Peneliti Teknologi Teknik Indonesia, 2024)
This extensive study explores the environmental impact of electric vehicles (EVs) powered by renewable energy sources. This review also looks at how they might lessen air pollution, cut carbon emissions, and support environmentally friendly transportation networks. Renewable energy-powered electric cars (EVs) have become a viable substitute for conventional internal combustion engine automobiles as the globe moves toward greener energy sources and looks for ways to tackle climate change. This essay examines how adopting EVs would affect the environment, with particular attention to resource use, air quality gains, and greenhouse gas emissions. It examines how EVs' life cycle emissions compare to those of conventional cars, taking into account things like how cars are made, how electricity is produced, and how end-of-life disposal is handled. The study also looks at how renewable energy sources like solar, wind, and hydropower can be integrated into the electrical grid to power electric vehicles (EVs), emphasizing the mutually beneficial effects on the energy and transportation sectors. The study also addresses the possible opportunities and problems that come with the widespread use of EVs powered by renewable energy, including infrastructural needs, legislative incentives, and customer behavior. This study aims to provide important insights into the environmental implications of EVs powered by renewable energy, guiding decision-making processes, and shaping future strategies for sustainable transportation and energy transitions through a thorough analysis of the body of existing literature, empirical studies, and modeling approaches.